Analisis karya tulis ilmiah dosen Institut Pertanian Bogor terindeks Scopus sampai tahun 2021 - Komalasari, Rita (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2021)
ABSTRACT Librarians, as information’s manager, must be able to take advantage of all available sources of information, both printed and electronic, relevant and uptodate present information. They have to be able serve information to the academic community in both printed and/or electroric documents. Information about scientific papers produced by IPB University Lecture or researcher are very important and o fcourse useful for the progress of research in the future. One of the tools to determine the development of research that has been carried out by IPB University lecturers or to examine the trend researchs is scopus .com. The purpose of this study is to determine the profile of IPB University Lecturers’s scientific paper indexed by scopus until 2021. In this study, will be presented information and analysis of documents based on subject, documents by author, by years, by country or territory and based on funding sponsors. The method used in this study is a review analysis of the subscribed scopus databased at the IPB University Library. The analysys showed that agricultural and biological science, occupied the top rank with 3674 documents, followed by environmental sciences with 3038 documents. Documents basen on subjec area, occupy by environmental sciences with score 23, 8%. Document by type is Articles that occupied the top rank, with score 50,6%. Keywords: Librarian; information managers; scientific papers; IPB Lecturer; scopus.com